Philosophy, rhetoric, and sophistry in the high Roman Empire : Maximus of Tyre and twelve other intellectuals - Lauwers, Jeroen. (Mnemosyne, Supplements, 2015)
How is it possible that modern scholars have labelled Maximus of Tyre, a second-century CE performer of philosophical orations, as a sophist or a 'half-philosopher', while his own self-presentation is that of a genuine philosopher? If we take Maximus' claim to philosophical authority seriously, his case can deepen our understanding of the dynamic nature of Imperial philosophy. Through a discursive analysis of twelve Imperial intellectuals alongside Maximus' dialexeis , the author proposes an interpretative framework to assess the purpose behind the representation of philosophy, rhetoric, and sophistry in Maximus' oeuvre. This is thus as yet the first book-length attempt at situating the historical communication process implicit in the surviving Maximean texts in the concurrent context of the Imperial intellectual world.